From earth to emissions reduction-Clays in the journey toward low-carbon cements - Gómez-de-la-Torre, María de los Ángeles; Koufany, Imane; Santacruz-Cruz, María Isabel; Rodríguez-Ruiz, María Dolores; García-Aranda, Miguel Ángel (My University, 2026)
Reducing the carbon footprint of cement sector requires rethinking its fundamental ingredient: Portland clinker. One of the most promising pathways is the incorporation of supplementary cementitious materials (SCMs), with limestone calcined clay cements (LC3) standing out as a particularly effective family of low-carbon binders. Among these, the LC3-50 formulation, consisting of roughly 50 wt% Portland clinker, 30 wt% (thermally) activated clay, 15% limestone, and 5% gypsum, has gained remarkable attention for combining performance and sustainability, although research to date has focused predominantly on systems based on thermally activated kaolinitic clays [1]. This blend can achieve up to a 40% reduction in CO₂ emissions compared to conventional cement, while still delivering high compressive strength after 7 days and strong resistance to chloride and sulfate ingress. Yet, LC3-50 is not without its limitations: early-age (1-day) strength remains modest, workability declines within the first hours, and carbonation resistance can be lower than desired. Ongoing research addresses these challenges through the fine-tuning of admixtures and curing regimes. After introducing the fundamental concepts of low-carbon cements, pozzolanic reactions, and the mineralogy of phyllosilicates, this work examines recent advances in both thermal and mechanochemical activation of clays, not only kaolinite but other types such as 2:1 clays. It further proposes general correlations useful for predicting compressive strength development [2,3]. The contribution will include the main scientific and practical challenges that must be overcome for the large-scale deployment of these “old minerals with new purpose,” transforming familiar clays into high-performance, sustainable cement constituents.
Keywords: Cemento; Supplementary cementitious Materials (SCMs)